Analysis of binge-watching on streaming services by Peruvian young adults - Sambuceti Aspillaga, Paolo Stefano (2022)
This research analyzes the consumption of series by binge-watching on streaming platforms through the Theory of Uses and Gratifications to understand the motives, needs and gratifications obtained from users when performing such practice, as well as the active cognitive processes that occur with the decision of what content to watch and at what time. Analyzing the gratifications sought, sensations and use of streaming platforms will help to understand the binge-watching behavior of young adults. In order to carry out the study, a qualitative approach with phenomenological design was used to obtain the description of experiences of the individuals and causes that influence the phenomenon of compulsive consumption of series and movies.